New generating functions for multivariate biorthogonal polynomials on the N-sphere. (1995) - Exton, Harold
Abstract : Certain multivariate biorthogonal polynomials on the N -sphere arise in connection with quantum chromodynamics. These functions can be expressed in terms of Lauricella functions of the first kind, and multi-dimensional generating functions for them are deduced by means of an extension of Bailey's theorem.